ANALYSIS OF THE EFFECT OF ADVERTISING, QUALITY AND BRAND IMAGE ON SALYCIL POWDER PRODUCTS ON BRAND TRUST AND CUSTOMER LOYALTY AT PT - Ria Rezki Botutihe; Sahat Saragi; Lies Putriana (SEAN Institute, 2023)
Dermatitis is a disease that often disturbs people's health in tropical countries like Indonesia. The main symptom of dermatitis is itching, which is an irritating skin sensation that stimulates scratching. Treatment of itching is through a pharmacological approach using salycil powder. This research aims to analyze the influence of advertising, quality and brand image of salicyl powder products on brand trust and customer loyalty at PT A questionnaire with a closed question design was used as a research instrument, and a total of 105 respondents were sampled in the research. The multiple linear regression method was used as a data analysis technique, the SPSS 20 for Windows program was used to analyze the data obtained after the research.